Strengthening the Culture of Democracy and Human Rights to Prevent Conflicts and Wars - Tak, Ziad (European Scientific Journal, ESJ, 2019)
This paper focuses on investigating the relationship between democracy and the respect for human rights, to underpin the culture of human rights, and to establish democratic societies that enable individuals and groups to treat their conflicts by the use of peaceful methods. Therefore, the focus of this paper is to produce suggestions and solutions for enhancing and consolidating democracy, to be more integrated into the three main pillars of the United Nations (Peace and Security, Human Rights, and development), and to consider democracy as a fundamental right. Our research is based on a historical and empirical study which proved that a significant relationship exists between Human rights violation and conflicts.